2018
DOI: 10.1002/cam4.1335
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor 2: a poor prognostic biomarker linked to racial disparity in women with uterine carcinosarcoma

Abstract: The objective of this study was to investigate the relationship of insulin‐like growth factor 2 (IGF2) expression and survival in women with uterine carcinosarcoma (UCS). Insulin‐like growth factor 2 protein expression was determined by immunohistochemical staining of tumor tissues from 103 patients with UCS. The H‐score (product of staining intensity and percentage positive cells) was quantified for the epithelial cytoplasmic (EC), epithelial nuclear (EN), and malignant stromal compartments. Multivariable Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This evidence also indicates that activation of the IGF-II locus may promote EMT [191] that could then facilitate tumor invasion and metastasis. This is consistent with reports that IGF-II is associated with progression and prognosis [193,194,195,196]. A further implication of the reactivated developmental program is related to the splice variant of the insulin receptor, IR-A, which was originally reported to be highly expressed in fetal and cancer cells [77].…”
Section: Igf-ii Locus and Cancersupporting
confidence: 89%
“…This evidence also indicates that activation of the IGF-II locus may promote EMT [191] that could then facilitate tumor invasion and metastasis. This is consistent with reports that IGF-II is associated with progression and prognosis [193,194,195,196]. A further implication of the reactivated developmental program is related to the splice variant of the insulin receptor, IR-A, which was originally reported to be highly expressed in fetal and cancer cells [77].…”
Section: Igf-ii Locus and Cancersupporting
confidence: 89%
“…High insulin growth factor 2 (IGF2) expression is associated with chemotherapy resistance and is a candidate factor that could contribute to the worse treatment responses of Black compared with White patients with USC. Immunohistochemical analysis of 103 USC specimens found a higher IGF2 expression in Black compared with White patients, and a race-stratified multivariate analysis found that high IGF2 expression in the epithelial component of the tumors more than doubled the risk of death in Black women [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…This reflects longstanding evidence that even after controlling for socioeconomic and pathologic characteristics, the black race is still associated with worse outcomes. 32 Existing literature has shown that certain cellular pathway proteins such as p53, HER2/Neu, and IGF2 exist in increased concentrations in black versus non-black patients and are associated with worse survival, [33][34][35] but additional poorly understood molecular mechanisms may be at play. Consequently, future studies should consider evaluating the molecular subtypes for black patients with locally advanced endometrial cancer focusing on microsatellite instability.…”
Section: Discussionmentioning
confidence: 99%